Caracterização da participação social e preditores da restrição da participação social em adultos com Síndrome de Down - Andrade, Michele Lacerda de (2021)
Objective: To characterize social participation and identify the predictors of social participation in adults with Down Syndrome (DS). Methodology: Cross-sectional study, 60 adult individuals with DS, 28.27±7.25 years old, were evaluated. To characterize social participation, the Assessment of Life Habits (Life-H 3.1) was applied. To identify the predictors of social participation, instruments associated with the Body Function and Structure, activity, environmental and personal factors components of the ICF biopsychosocial model were chosen. These instruments were the Body Mass Index (BMI), the Mini Mental State Examination (MMSE) for mental function, the Stand up and sit down test to assess lower limb muscle strength, the 8 foot up and go test (8-FUGT) to assess functional mobility, Measure of the Quality of the Environment (MQE) and age. Data analysis: To characterize the sample and social participation, a descriptive analysis was performed and to identify the predictors, the Multiple Linear Regression analysis was used. Results: The Life-H total score shows that individuals present a moderate restriction in Social participation, being the best performance in items involving Daily Activities, and presented a greater restriction in the Employment, Education and Responsibilities domains, which are within the Roles Social. Three variables were found to predict social participation, with 8-TUGT being the best predictor, followed by MEEN and the Sit and Stand Test. Conclusion: This study showed that individuals with DS have a greater restriction in Social Participation in activities involving Social Roles. The best predictors influencing Social Participation were functional mobility, cognition and lower limb muscle strength.